Prediction of the yield stress of concrete considering the thickness of excess paste layer. (10th June 2018) - Lee, Jin Hyun; Kim, Jae Hong; Yoon, Jin Young
Highlights: A model to predict the yield stress of concrete is proposed adopting the excess paste theory. The thickness of excess paste is assumedly constant for fine and coarse aggregates while it is dependent on the properties of binder. A concrete equivalent mortar having 90%-volume-fraction aggregates content in concrete mix or a wet-sieved mortar can be used to measure the yield stress of the corresponding mortar. Finally, based on the measured yield stress of the corresponding mortar, the model acceptably predicts the yield stress of a concrete mix. Abstract: Polycarboxylates in chemical admixtures are adsorbed onto the surface of cement particle, and the degree of their adsorption is related to the performance of concrete. Measuring total organic carbon (TOC), we demonstrated the amount of the consumed carbon is consistent regardless of the existence of aggregates. This result allows us to consider the effect of aggregates inclusion in a superplasticized cement paste. In a multiscale approach, concrete or mortar is considered as suspension of aggregates in cement paste. Excess paste layer covering aggregates in cement-based materials is considered taking a material property of the layer thickness in addition to the volume fraction of the aggregates. Finally, the yield stress of mortar or concrete can be predicted assuming that the layer thickness is constant regardless of the aggregate volume fraction.